Capital formation and financial intermediation: The role of entrepreneur reputation formation - Li, Emma; Martin, J. Spencer (Journal of Corporate Finance, 2019)
Recently a new type of institution has emerged, crowd funders. These entities: 1) channel capital to create intellectual property; 2) gather information on project and entrepreneur quality; and 3) gauge demand information directly from individuals to improve the efficiency of capital allocation. Data from crowd funder Kickstarter allows new insights on capital formation and the role of entrepreneurial reputation formation in the venture funding process. This funding method includes all cases where entrepreneurs try yet fail to raise funds, a feature heretofore unavailable to researchers. We find that both positive and negative reputation acquisition significantly change measures of capital raising success.